2017
DOI: 10.3892/ijmm.2017.2998
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 modulates hypoxia-induced endothelial-to-mesenchymal transition of human cardiac microvascular endothelial cells

Abstract: Endothelial-mesenchymal transition (EndMT) is an essential mechanism in the cardiovascular system, for both cardiovascular development and cardiovascular diseases (CVDs). Recent studies indicate that runt-related transcriprunt-related transcription factor 3 (RUNX3) contributes to EndMT and endothelial cell dysfunction. However, the underlying molecular mechanism remains unknown. The present study was designed to investigate the role of RUNX3 in EndMT and endothelial cell function, and to elucidate the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Immunofluorescence results ( Figure 1 D) further showed that CD31 + α-SMA/FSP1 + cells or CD31 − α-SMA/FSP1 + cells were found in the hypoxia groups, and CD31 + α-SMA/FSP1 − cells were found in the normoxia group. All these changes were time dependent (results not shown), similar as shown in our previous studies [ 27 ]. Taken together, these data demonstrated that hypoxia induced EndMT.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Immunofluorescence results ( Figure 1 D) further showed that CD31 + α-SMA/FSP1 + cells or CD31 − α-SMA/FSP1 + cells were found in the hypoxia groups, and CD31 + α-SMA/FSP1 − cells were found in the normoxia group. All these changes were time dependent (results not shown), similar as shown in our previous studies [ 27 ]. Taken together, these data demonstrated that hypoxia induced EndMT.…”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure 4 A,B, hypoxia up-regulated TGF-β2, p-Smad2, and p-Smad3, which suggested that hypoxia induced EndMT in HCMECs by activating TGF-β signaling pathway, consistent with recent studies [ 27 ]. Snail is the key transcription factor in the downstream of TGF-β signaling pathway.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations